Towards a Shi'i Mediterranean empire : Fatamid Egypt and the founding of Cairo : the reign of the Imam-calip al-Mu'izz from Taqī al-Dīn Aḥmad b. 'Alī al-Maqrīzī's Itti'āẓ al-ḥunafā' bi-akhbār al-a'imma al-Fāṭimiyyīn al-khulafā' /: Fatamid Egypt and the founding of Cairo : the reign of the Imam-calip al-Mu'izz from Taqī al-Dīn Aḥmad b. 'Alī al-Maqrīzī's Itti'āẓ al-ḥunafā' bi-akhbār al-a'imma al-Fāṭimiyyīn al-khulafā'. (2009) - Unknown
No abstract available